Suggested Guidelines to Prevent Health Difficulties and Risk Behavior among Students of Secondary Schools in Governorate of Cairo - Nadia Abdel Latif Ali (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Adolescence is a phase of exposure to several risk behaviors which lead to high morbidity ratesand different health issues. Study aim: To evaluate the communal health difficulties and risk behavior amongsecondary school students and to suggest health guidelines for students to minimize these risk behaviors.Subject and Methods: correlational design as descriptive was used in the current work. Setting: The currentwork pereformed at 2 secondary schools: El-Saneya secondary school for girls and El- Khedewey secondaryschool for boys – Governorate of Cairo . Sample: 180 students were randomly selected from first and secondsecondary grades from each school. Tools: three parts questionnaire sheet was prepared part I: demographicstudents characteristic, part II: communal health difficulties (social, physical, and psychological), part III:common risk behavior executed via secondary school students. Results: respiratory difficulties (25%), skindifficulties (45.8%). Regarding psychological difficulties (61.1%) of students reported that they complainof inability to communicate well with others, while (66.7%) complain of low self-esteem. Social healthdifficulties were having difficulties with parents at home and with their colleagues at school. The mostcommon risk behaviors were as follow: 25% of students smoke tobacco, 60% of them engaged in physicalviolence, while 42.2% have unhealthy dietary behavior. Smoking was positively correlated along age(p= 0.001). Conclusion: The mostly communal risk behavior found was smoking tobacco, engagementin physical violence, and having unhealthy dietary habits. There was significant relation among students’age & gender and common risk factors as: drug use, smoking, violence involvement, eating fast foodand non-participation in activities. Recommendation: Dissemination of health guidelines for secondaryschool students to prevent health difficulties and application of health education programs to raise students’awareness regarding how to prevent risk behaviors.